Similitudes y diferencias en la cultura laboral Mexicana: Elementos compartidos en equipos de organizaciones de diferente desempeño (Similitudes and differences of Mexican work culture: Shared elements in workgroups from organizations of different performance) - Mendoza Gómez, Joel; Rositas Martínez, Juan (Facultad de Contaduría Pública y Administración U.A.N.L., 2011)
Abstract: In this paper, the results of a study about the Mexican work culture are presented, by utilizing the identification of elements of the frame of reference or mental model of workers in Mexican organizations. Recognizing the progress of the study of Mexican work culture because of its importance, we considered convenient to proceed studying this topic, results are presented about share mental model among the duality of work culture – social culture. The conclusions of the study reinforce the existence of similitudes and differences on the Mexican work culture that shows the influence of the national culture. Resumen: En este trabajo, se presenta un estudio de la cultura laboral mexicana, mediante la identificación de elementos del marco de referencia o la forma de pensar de trabajadores de organizaciones mexicanas sobre el aspecto laboral. Aún cuando existen avances en el estudio de la cultura del trabajo en México, debido a la importancia de este tema, es conveniente continuar avanzando en estudios que permitan ir clarificando la tendencia de la cultura de trabajo. Los resultados obtenidos reflejan la existencia de similitudes y diferencias en la cultura laboral mexicana que reflejan la influencia de la cultura nacional o social en dicha cultura.